LESSON STUDY AS AN ALTERNATIVE DEVELOPMENT FOR PRE-SERVICE TEACHER COMPETENCE - Wardani Dwi Wihastyanang (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2017)
Lesson Study is not learning model but a model of teachers' professional development through the study of collaborative learning and sustainable as well as carrying the principles of collegiality and mutual learning to build a learning community (Hendayana, et al., 2006). This Study conducted a library research through a review of journal article that discuss about lesson study. As a model of development, lesson study widely adopted by teachers in Indonesia but its implementation procedures have been amended in accordance with the context and situation. Lesson Study is also potentially be applied to the Real Teaching (PPL) for students LPTKs, but need a clear implementation guidelines and operational for students, teachers, professors, and school.